New stuff or better ways: What matters to access international markets? - Adriana Peluffo; Inmaculada Martínez-Zarzoso; Ernesto Silva (Journal of Applied Economics, 2020)
The connection of innovation and exporting is of major interest to developing countries aiming to achieve higher growth and wellbeing. This study analyzes whether different types of innovation affect export behavior at the firm level for an unbalanced panel of Uruguayan manufacturing firms. Logistic regression and matching with difference-in-differences (MDID) techniques are applied to data from 2003 to 2012. Unlike other studies, productivity-enhancing (or cost-reducing) innovation shows a stronger correlation with exporting than product innovation, indicating that price competition is more important than quality competition for Uruguayan products in foreign markets. Furthermore, using MDID we establish a direct causal link from innovation to exporting. Finally, the causal effect of innovation on exporting is mainly found for exports to countries belonging to the regional trade agreement Mercosur. Overall, the findings indicate that active innovation policies along with other export promotion policies would help promote firms' participation in foreign markets.
Keywords: 330; dif in dif; exporting; matching; process innovation; Product innovation